A new species of Macroclinium (Orchidaceae: Oncidiinae) from Andean Venezuela with brief comments on the biogeography of the genus - Fernández-Concha, German Carnevali; Cetzal-Ix, William (Phytotaxa, 2015)
A new species of Macroclinium (Orchidaceae, Oncidiinae) is described and illustrated from the Venezuelan Andes. Macroclinium larense is related to M. borjaense but is readily diagnosed by its wider isthmus, which is about as long as broad whereas it is conspicuously narrower in M. borjaense; furthermore, sizes and proportions of other floral organs are also different. The new species is only known from the Yacambú National Park in Lara state. An identification key and a distribution map of the species of Macroclinium present in Venezuela are provided. Finally, a brief biogeographical consideration of the genus is presented.